GENDER SPEECH DIFFERENCES IN USING LANGUAGE: A CASE STUDY OF STUDENTS AT UPB LANGUAGE CENTER OF UIN SULTHAN THAHA SAIFUDDIN JAMBI - Chyntia Damayanti; Rahmadhani Putri (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This research aims to find out and analyze what speech differences exist between male and female. This research is to find out the uniqueness of the speech of male and female participants in the speak out course class. This research focuses on three aspects of differences, namely differences based on attitude, vocabulary differences, and non-verbal language differences. This research was conducted at language center namely UPB Telanaipura. Researchers used qualitative methods, and found differences in speech between male and female participants during class hours or when interviewed. The subjects in this research were the “Speak Out class program’’. There are 6 participants, they are 3 male and 3 female. In the data collection method, the researcher used observation and interview techniques. During the observation and interview, the researcher found speech differences between male and female and their uniqueness. The differences based on attitude, female tend to use sentences or actions that are soft and polite because basically female are known for their softness and politeness. For vocabulary, female tend to use adjectives more often and produce more words to explain something. The last differences based on non-verbal, the differences between male and female are still related to language, namely gestures and accompanying facial expressions.